An experimental study on the behavior of segmental pile with variable flexural rigidity - Yahia, Yasser İbrahim Osman. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
Alternating mortar blocks and rubber pads are connected to each other by a cable passing through the center of each block to form a fixed beam/pile model with variable flexural rigidity. The fixed beam/pile model is supported on manufactured springs with 1K, 2K and 3K ( K=4 N/mm) spring constants to partially represent sandy soil at different relative densities. Varying tension loads are applied to the cable to achieve desired flexural rigidity for the fixed beam/pile model. Three point beam tests are conducted and the load-deflection behavior is recorded, from which representative flexural rigidity values are obtained. All other fixed beam/pile model tests are conducted on spring supports by applying load from the end (top) and middle section of the beam and measuring load and deflection at the load application point. Static and cyclic loads are applied to reach a maximum displacement of 4 mm. In addition prescale films are placed at five locations at the rubber mortar interfaces. These films are scanned, calibrated and with the help of a software the contact stress maps are obtained. From the measured deflections, corresponding spring forces are determined. From the spring reaction forces, the boundary conditions are obtained and integrated to obtain the shear forces. With the second integration moment values are determined. The stress maps obtained from prescale films are used to backcalculate the moment distribution along the fixed beam. The comparision of the moment distribution showed a similar trend with the experimental findings. The magnitude of the moment obtained from the backcalculation of prescale stress maps are upto two times of that obtained from the load-deflection measurements which is due to small number of deflection measurements which underestimated the beam curvature.
Keywords: Girders -- Design and construction..